8.5k views
1 vote
{y = 3x -1
{x-y = - 9

User Joe Lloyd
by
6.0k points

2 Answers

1 vote
always make sure both the equations have equal notations so 3x-y=1 and x-y=0
after the that u may use the normal simultaneous eqn and find values of x and y
User Couchy
by
6.0k points
5 votes
Here, substitute the value of y from equation 1 into equation 2,
x - y = -9
x - (3x - 1) = -9
x - 3x + 1 = -9
-2x = -9 - 1
x = -10/-2
x = 5

Now, substitute the value in 1st equation,
y = 3(5) - 1
y = 15 -1 = 14

In short, Your Answer would be: (5, 14)

Hope this helps!
User Ramkumar Singh
by
6.0k points